Seroprevalence of Fowl Pox Antibody in Indigenous Chickens in Jos North and South Council Areas of Plateau State, Nigeria: Implication for Vector Vaccine - Adebajo, Meseko Clement (International Scholarly Research Network, 2012)
Fowl pox is a viral disease of domestic and wild birds. The large size of the genome makes it a useful vector for recombinant DNA technology. Although the disease has been described in both commercial and indigenous chickens in Nigeria, data are limited on seroprevalence in free range chickens. Such data are, however, important in the design and implementation of fowl pox virus vector vaccine. We surveyed current antibody status to fowl pox virus in free range chickens by testing 229 sera collected from 10 villages in Jos North and Jos South LGA of Plateau State Nigeria. Sera were analyzed by AGID against standard fowl pox antigen. Fifty-two of the 229 (23%) tested sera were positive for fowl pox virus antibody, and the log titre in all positive specimen was >2. Thirty (21%) and twenty-two (27%) of the samples from Jos South and Jos North, respectively, tested positive. This was, however, not statistically significant (P = 0.30). Generally the study showed a significant level of antibody to fowl pox virus in the study area. This observation may hinder effective use of fowl pox vectored viral vaccine. Fowl pox control is recommended to reduce natural burden of the disease.